2017
DOI: 10.3390/sports5010012
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Agility, Speed and Endurance Performance in Young Elite Soccer Players

Abstract: The aim of this study was to investigate changes in the linear running speed (LRS) for 30 m, change of direction speed (CODS), and endurance in young elite Czech soccer players. The following tests were conducted to assess CODS and endurance: Agility 505 turning toward the dominant (A505DL) and non-dominant lower limb (A505NL); Illinois Agility Test (IAT); and intermittent test (Yo-Yo IRT1). During the soccer season, we investigated performance at the following time periods: the start (t1) and the end of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 21 publications
7
59
3
5
Order By: Relevance
“…For example, while some studies reported significant improvement in speed and power performances throughout the preseason period, and a further improvement until the middle or the end of the competitive season [ 7 , 8 ], others reported improvement during the preseason with no further changes during the competitive season [ 5 , 9 , 10 ]. In the same line, while aerobic fitness was found to be significantly improved during the preseason phase in all relevant studies, some of them reported stagnation in this variable throughout the competitive season [ 8 , 11 ], whereas others reported increases [ 12 , 13 ] or decreases [ 14 , 15 ] during that period. One reason for these inconsistencies may be the differences between the participants since some studies tested professional players [ 9 , 15 , 16 ] while others examined semi-professional adult [ 12 ] or young [ 7 , 13 ] players.…”
Section: Introductionmentioning
confidence: 74%
“…For example, while some studies reported significant improvement in speed and power performances throughout the preseason period, and a further improvement until the middle or the end of the competitive season [ 7 , 8 ], others reported improvement during the preseason with no further changes during the competitive season [ 5 , 9 , 10 ]. In the same line, while aerobic fitness was found to be significantly improved during the preseason phase in all relevant studies, some of them reported stagnation in this variable throughout the competitive season [ 8 , 11 ], whereas others reported increases [ 12 , 13 ] or decreases [ 14 , 15 ] during that period. One reason for these inconsistencies may be the differences between the participants since some studies tested professional players [ 9 , 15 , 16 ] while others examined semi-professional adult [ 12 ] or young [ 7 , 13 ] players.…”
Section: Introductionmentioning
confidence: 74%
“…The bigger increase in the first researched period is due to implicated methodology for speed endurance development (Пеев, 2017). In support of this statement are the researches of Swilowski et al (2013) and Dragijsky et al (2017) who point out that the trainings influence the results of these kind of researches.…”
Section: Discussionmentioning
confidence: 85%
“…Studies examining anaerobic fitness changes during the pre-season training period demonstrated inconsistent results. Whereas some studies reported significant improvement in speed, power and agility performance 10 28 , others failed to find such improvement 29 36 . The inconsistency in these studies may result from differences in the training programs and the population studied (professional compared to semi-professional adult or youth players).…”
Section: Discussionmentioning
confidence: 99%
“…These results emphasize the importance of the pre-season training period not only for the necessary fitness enhancement needed to compete at a high level during the demanding soccer season but also for injury prevention during the following competitive season among professional soccer players. It is possible that only the changes in VO 2 max (and not other measured fitness components) were associated with injury rates because pre-season soccer training focuses on and is known to improve mainly aerobic fitness characteristics 24 , whereas the effect of pre-season training on speed, power and agility performance has demonstrated conflicting results 10 29 .…”
Section: Discussionmentioning
confidence: 99%